Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja, terhadap Kinerja Guru melalui Kepuasan Kerja sebagai Variabel Intervening di SMP Swasta Sekecamatan Binjai Selatan - Waskito Waskito; Akrim Akrim; Irvan Irvan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to test and analyze whether there is an influence of Principal Leadership and Work Motivation on teacher performance through Job Satisfaction as an intervention variable in Private Middle Schools in South Binjai District. Thesis 2022. The method used in this study is a quantitative method. The population in this study amounted to 44 people, while the sampling technique used was the total population. with a total sample of 44 people. The data collection tool used is a questionnaire measured by a Likert scale and using path analysis techniques (Path Analysis). Based on the test results it can be concluded that the principal's leadership has a positive and significant influence on job satisfaction (H1 is accepted), work motivation has a positive and significant influence on job satisfaction (H2 is accepted), the principal's leadership has a positive and significant influence on teacher performance (H3 Accepted), work motivation has a positive and significant effect on teacher performance (H4 is accepted), job satisfaction has a positive and significant effect on teacher performance (H5 is accepted), principal leadership has a positive and significant effect on teacher performance with job satisfaction as an intervening variable (H6 is accepted), Work Motivation has a positive and significant effect on teacher performance with job satisfaction as an intervening variable (H7 is accepted). In conclusion, there is a significant influence between the principal's leadership and work motivation on teacher performance through job satisfaction as an intervening variable. Keywords: job satisfaction, principal leadership, teacher performance, work motivation.